The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2ra00599a
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic framework bearing new viologen ligand for ammonia and Cr2O72− sensing

Abstract: Three MOFs based on different metal salts were synthesized, and metal salts were found to play a key role in regulating the performance of MOFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The fluorescence quenching intensity of MOF- 1 and MOF- 2 , and the concentration of Cr 2 O 7 2− ions could be well fitted with the Stern–Volmer equation in the low concentration region. 48 Emission intensities have been fitted in the same way. 37 The K sv values of MOF- 1 and MOF- 2 , as determined using the Stern–Volmer equation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence quenching intensity of MOF- 1 and MOF- 2 , and the concentration of Cr 2 O 7 2− ions could be well fitted with the Stern–Volmer equation in the low concentration region. 48 Emission intensities have been fitted in the same way. 37 The K sv values of MOF- 1 and MOF- 2 , as determined using the Stern–Volmer equation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Volmer equation in the low concentration region. 48 Emission intensities have been fitted in the same way. 37 The K sv values of MOF-1 and MOF-2, as determined using the Stern-Volmer equation (Fig.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…3(A)–(C), left). 49 LMOFs 4–6 were synthesized by solvothermal heating using different metal salts (ZnNO 3 for 4 , ZnCl 2 for 5 , and ZnSO 4 for 6 ), and these LMOFs were structurally characterized by X-ray diffraction analysis which revealed that each MOF structure is built from binuclear metal building units, which are coordinatively connected to two protonated BTEC 4− ligands and three Zn( ii ) ions. The extended structures of LMOFs results in the formation of a porous channel that acts as a host to accommodate the guest, 4-BCBPY 2+ cyano-viologen, into it to achieve charge balance.…”
Section: Metal–organic Framework (Mof)-based Fluorescence Chemosensorsmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) have unique structures [1][2][3][4] and extensive applications, such as sensing, [5][6][7][8][9] catalysis, [10][11][12] adsorption, 13 separation, [14][15][16][17] biomedical imaging, [18][19][20] etc. Photochromic MOFs are an important type of MOFs and have very promising applications, such as metal oxidation state modulation, 21 erasable printing without ink, 22 conductivity, 23 anticounterfeiting, 24 sensing, 25,26 etc.…”
Section: Introductionmentioning
confidence: 99%